FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENGISIAN PARTOGRAF SECARA LENGKAP OLEH BIDAN PRAKTEK MANDIRI DI WILAYAH KERJA PUSKESMAS LUBUK BEGALUNG PADANG TAHUN 2019 - rini febrianti (MIDWIFERY HEALTH JOURNAL, 2019)
Monitoring and recording of the condition of the mother and fetus in labor using partographs is an effort to reduce MMR and IMR. At present, partographs have not been implemented properly so that not all labor is monitored with partographs, as a result the abnormalities and complications that occur during labor are not detected early and clinical decision making cannot be performed. Based on reports from the DKK Padang in December 2018, it was still found that 25% of the incomplete partographs were filled out by independent midwives. From 2141 deliveries at the Lubuk Begalung Health Center. The study used analytic survey with cross sectional design. The study population was all independent practice midwives (BPM) who were in the work area of ​​the Lubuk Begalung puskesmas in the amount of 31 BPM and samples were taken with the total population. Data collection using a questionnaire with interviews on July 4 to August 5 2019. The results showed 45.2% incomplete partographs filling, have a low level of knowledge 25.8%, have a negative attitude 22.6%, and 83.9% no supervision. After being tested with Chi-Square found that there was a significant relationship between the level of knowledge, attitude, supervision with complete partograph filling (p <0.05). There is still a low level of supervision from the coordinating midwife in completing partographs in full by the Independent Practice Midwife. It is hoped that the coordinating midwife can increase supervision or supervision of the Mandiri practice midwife to complete the pertographs.